1995
DOI: 10.1046/j.1471-4159.1995.65041651.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stimulatory Effect of Estradiol on Striatal Dopamine Synthesis

Abstract: The acute effect of physiological doses of estradiol (E2) on the dopaminergic activity in the striatum was studied. In a first series of experiments, ovariectomized rats were injected with 17α or 17β E2 (125, 250, or 500 ng/kg of body weight, s.c.), and in situ tyrosine hydroxylase (TH) activity (determined by DOPA accumulation in the striatum after intraperitoneal administration of NSD 1015) was quantified. A dose‐dependent increase in striatal TH activity was observed within minutes after 17β (but not 17α) E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(80 citation statements)
references
References 31 publications
2
77
0
1
Order By: Relevance
“…Second, we did not test female participants within a fixed window of the menstrual cycle, which could impact Now bias (Smith et al 2014). However, this concern is somewhat mitigated by the fact that the FMT-PET measures used in these analyses may be downstream of the hormonal effects Kohama 1998, 1999;Pasqualini et al 1995;Shansky et al 2004;Xiao and Becker 1994) and thus predict Now/Later choice behavior independent of cycle phase. Regardless, these data add significantly to our existing model that frontal DA modulates Now bias according to a U-shaped function (Altamirano et al 2011;Kelm and Boettiger 2013;Smith and Boettiger 2012;Smith et al 2014) by identifying roles for specific extrastriatal DA terminal fields in modulating Now bias.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not test female participants within a fixed window of the menstrual cycle, which could impact Now bias (Smith et al 2014). However, this concern is somewhat mitigated by the fact that the FMT-PET measures used in these analyses may be downstream of the hormonal effects Kohama 1998, 1999;Pasqualini et al 1995;Shansky et al 2004;Xiao and Becker 1994) and thus predict Now/Later choice behavior independent of cycle phase. Regardless, these data add significantly to our existing model that frontal DA modulates Now bias according to a U-shaped function (Altamirano et al 2011;Kelm and Boettiger 2013;Smith and Boettiger 2012;Smith et al 2014) by identifying roles for specific extrastriatal DA terminal fields in modulating Now bias.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have consistently shown that physiological concentrations of estradiol stimulate dopamine synthesis/release in striatal tissue (Becker, 1990;McDermott, 1993;Pasqualini et al, 1995Pasqualini et al, , 1996. Moreover in rats, high levels of estradiol at estrus were associated with significantly higher levels of amphetaminestimulated striatal dopamine release than at diestrus (Becker and Cha, 1989).…”
Section: Lh and Gonadal Steroid Interactionsmentioning
confidence: 99%
“…There is also evidence that membrane effects of estrogens can activate intracellular signaling pathways involving cyclic AMP (cAMP; [103,170,254]), protein kinase A (PKA; [104,141,266]), the "mitogen activated protein kinases" (or MAP kinases; [39,122,153,205,260,269,276]), and the tyrosine kinases [39]. The activation of these intracellular signaling pathways results primarily in phosphorylations/dephosphorylations producing different kinds of physiological responses such as the decoupling of a receptor from its effector system [141,[171][172][173] or the modulation of the catalytic activity of an enzyme [191]. Finally, as mentioned previously, the activation of these cascades of intracellular events may result in a transcriptional activation caused, for example, by the phosphorylation of CREB (cAMP response element [CRE]-binding protein) which then acts at the level of the cAMP response element notably (CRE; [2,3,46,102,288]).…”
Section: Non-genomic Effects On Cell Functionmentioning
confidence: 99%